Rational Design of Dual‐State Emission Luminogens with Solvatochromism by Combining a Partially Shared Donor–Acceptor Pattern and Twisted Structures. Issue 70 (21st October 2019) - Qiu, Qianqian; Xu, Pengfei; Zhu, Yanjun; Yu, Junru; Wei, Mengru; Xi, Wenbin; Feng, Hui; Chen, Jianrong; Qian, Zhaosheng
Abstract: We report a general design strategy for a new class of luminogens with dual‐state emission (DSEgens) that are brightly emissive in both the solution and solid state, with solvatochromism properties, by constructing a partially shared donor–acceptor pattern based on a twisted molecule. The DSEgens with bright fluorescence emission in both the solid and solution state demonstrate a unique solvatochromism behaviour depending on solvent polarity and thus may have applications in anti‐counterfeiting. Abstract : Twisted chemistry ! A general design strategy for a new class of luminogens with dual‐state emission (DSE) and solvatochromism properties by constructing a partially shared donor–acceptor pattern based on a twisted molecule was reported (see figure).